Edukasi Inovasi Bisnis untuk Pelaku UMKM di Masa Post Pandemi Covid-19 - Rd. Heri Solehudin; Rudy Gunawan; Ulumuddin; Abdul Kodir; Aqiq Muttaqin; Lalu M. Tolkhah; Choirul Mahfuddin (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: In the current era, many people are faced with various conveniences on various platforms that are provided to obtain something without having to go to the seller's place or to the shop. One type of business that is in great demand or is often used on various digital platforms, namely the convenience of frozen food. Method: Qualitative method, while the data collection method uses interview techniques, direct observation. Results: This food business is also a very easy business, you could even say it's a business that can be done by everyone, even those who haven't been able to make it, it's just that it takes courage and also tenacity in managing the business like the efforts made by Mrs. Ema who opened a food business with a unique name, namely